Integrasi Edukasi Kesetaraan Gender, Kecerdasan Buatan, dan Kepemimpinan dalam Pengabdian Masyarakat Internasional untuk Pendidikan Berkelanjutan - Indrarini Dyah Irawati; Sari Dewi Budiwati; Runik Machfiroh; Augustina Asih Rumanti; Zuhanis Mansor; Izanoordina Ahmad (PELITA NUSA TENGGARA, 2026)
Sustainable development in the digital age requires women’s participation in technology, innovation, and leadership. However, a gender gap exists in access to technology education and the development of digital competencies, particularly for young women. Therefore, Telkom University and Universiti Kuala Lumpur (UniKL) are implementing a community engagement-based community service program to support women’s empowerment through gender education, technology literacy—particularly in Artificial Intelligence (AI)—and leadership development. The program will take place from May 5 to 11, 2026, targeting university students, young women, as well as female students and teachers at SMK Al-Amah Sindulang. Activities included a Studium Generale on gender policy and technology, an AI introduction workshop and hands-on practice with AI tools, as well as the Youth Leadership Academy. Program evaluation was conducted using a Likert-scale questionnaire and open-ended questions. The evaluation results show that the majority of participants responded positively, with 93% stating that the material was relevant to the event’s theme, 87% rating the timing as appropriate, 70.2% strongly agreeing that similar events should continue, and 76% strongly agreeing that AI literacy programs should be held again. In addition, participants also demonstrated an increased understanding of gender equality, technology literacy, and leadership, and showed a high level of interest in the development of digital technology particularly AI and future-ready skills. This program supports SDG 4, SDG 5, SDG 8, and SDG 17 by promoting digital literacy, empowering women, developing future-ready skills, and fostering international collaboration in education- and technology-based community engagement